Predictive value of serum uric acid on left atrial spontaneous echo contrast in non-valvular atrial fibrillation patients - Liao, Hong-Tao; Liu, Fang-Zhou; Xue, Yu-Mei; Zhan, Xian-Zhang; Fang, Xian-Hong; Huang, Jun; Wei, Wei; Rao, Fang; Deng, Hai; Liu, Yang; Lin, Wei-Dong; Wu, Shu-Lin (Journal of geriatric cardiology : JGC, 2015)
Objectives To investigate the relationship between serum uric acid （SUA） and left atrial spontaneous echo contrast （LA-SEC） in non-valvular atrial fibrillation （AF） patients. Methods We retrospectively screened 1,476 consecutive hospitalized patients with AF who underwent transesophageal echocardiography prior to radiofrequency catheter ablation, left atrial appendage closure and electric cardiover- sion at Guangdong General Hospital. Data on the clinical baseline characteristics of all patients were collected from electronic medical re- cords and analyzed. Results After exclusion of patients with left atrial thrombus, 1,354 patients entered into present study and 57 were LA-SEC. The mean female SUA level （380.88 ± 94.35 μmol/L vs. 323.37 ± 72.19μmol/L, P 〈 0.001） and male SUA level （416.97 ± 98.87 μmol/L vs. 367.88 ＋ 68.50 μmol/L, P = 0.008） were both significantly higher in patients with LA-SEC than in the controls. The mean left atrial dimension （41.32 ± 5.12 mm vs. 36.12 ± 5.66 mm, P 〈 0.001） was markedly larger in patients with LA-SEC. In multivariate regression analysis, SUA level was an independent risk factor for LA-SEC （OR： 1.008, P 〈 0.001）. In receiver operating characteristic curve analysis, the corresponding area under the curve for SUA predicting LA-SEC in female and male were 0.670 and 0.657, respectively. SUA level is significantly higher in non-valvular AF patients with LA-SEC. Conclusion SUA level is an independent risk factor and has a moderate predictive value for LA-SEC among non-valvular AF patients in Southern China.